G. Coedès y C. Archaimbault, Les Trois Mondes (Traibhūmi Brah R'vaṅ), Publications de L'École Française d'Extrême Orient, Volumen LXXXIX, École Française d'Extrême-Orient, Paris, 1973. - D., S. (Estudios de Asia y África, 1975)
-